مناقشة بحثية حول إمكانية تعليم القواعد النحوية من خلال النشاط (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Given the pursuit of excellence in second language (L2) teaching, this paper aims at discussing the issue of teaching grammar through game activities. Some definitions of grammar, followed by the place of grammar in L2 teaching will be introduced. In approaching games as a good way to teach grammar, some background information on games will be presented with regards to its place in language description nowadays. To give punch line in advance, what this paper will suggest is that games in language teaching must depend on such factors as the learners’ age and level, the motivation and interest in games, the size of group, the time devoted for the course and so on. This paper concludes that game activities, no matter how ingenious and sophisticated, are only one avenue of approach to improving language teaching. يتناول البحث المقدم مسألة تعليم قواعد اللغة من خلال النشاط والتي تستنبط أهميتها من السعي وراء التفرد في تعليم اللغة. وفقاً لذلك سيستعرض البحث بعض التعاريف النحوية, يتبعها التعريف بالمكانة التي يرتقيها النحو في مجال تعليم اللغة. سيركز البحث على الموازنة بين الصيغة و التطبيق. إن استخدام النشاط كوسيلة مجدية لتعليم القواعد النحوية, يدفع بالبحث إلى استعراض جدوى استخدام النشاط وتوضيح مكانته في مجال توصيف اللغة في الوقت الحاضر. يستخلص البحث عدة جوانب من أبرزها اعتماد النشاط في مجال تعليم اللغة على عدة ركائز, أهمها: عمر المتعلم ومستواه اللغوي، حافز المتعلم واهتمامه بالنشاط، عدد أفراد المجموعة الواحدة، الوقت المكرس للدورة الدراسية, وما إلى هنالك. في النهاية، يقدم البحث عدة اقتراحات من بينها أن النشاط ماهو إلا أحد السبل لتطوير تعليم اللغة وذلك بغض النظر عن صعوبته.